Analisis Kelayakan Usahatani Bawang Merah Di Desa Ngadiboyo Kecamatan Rejoso Kabupaten Nganjuk - Davina Azalia Erson; Fatchur Rozci (BiSTeK Pertanian, 2023)
Shallots are one of the important and strategic horticultural commodities in influencing the Indonesian economy, so it is necessary to carry out an agribusiness feasibility analysis that can provide an overview of whether the business is economically profitable so that it can be said that it is feasible or not feasible to continue doing it. This research was conducted for 3 (three) months from March to May 2023 on a demonstration plot in Ngadiboyo Village, Rejoso District, Nganjuk Regency. The purpose of this research is to analyze the feasibility of shallot farming in Ngadiboyo Village. The results showed that the shallot farming in Ngadiboyo Village was profitable with a total profit of IDR 13,948,150/season. From the BEP, the production BEP is 783 kg, the price BEP is IDR 7,322, the R/C value is 2.1, and the B/C value is 1,1. With these calculations it can be concluded that shallot farming in Ngadiboyo Village is feasible.